Immediate Effect of Kinetic Chain Activation and Mulligan’s Bent Leg Raise Technique in Patients with Asymptomatic Hamstring Tightness: A Randomised Clinical Trial - Santosh Channabasapa Metgud; Santosh D Patil; Omkar Anand Gaonkar (Journal of Clinical and Diagnostic Research)
Introduction: Hamstring shortness is an important mechanical marker for hamstring strain injuries, often related to a muscle imbalance between the quadriceps and hamstrings. Muscle tightness is considered a limiting factor for optimal performance, including individuals’ daily activities. Aim: To compare the immediate effects of the Kinetic Chain Activation Technique (KCAT) and Mulligan’s Bent Leg Raise (BLR) on hamstring tightness using the active knee extension test, diagnostic ultrasonography and the Sit and Reach Test (SRT) test. Materials and Methods: A randomised clinical trial was conducted in the Orthopaedic Manual Therapy Department of KAHER Institute of Physiotherapy, Belagavi, Karnataka, India, from December 2022 to June 2023. In this trial, subjects with asymptomatic hamstring tightness were enrolled and randomised into two interventional groups: KCAT (n=15) and BLR (n=15). Kinetic chain activation was applied to Interventional group A, while Mulligan’s BLR was applied to Interventional group B. Measurements were taken of the hamstring muscle’s length using the SRT test, the active knee extension test and diagnostic ultrasound to determine the immediate effects. To compare the length and thickness of the hamstring, AKT and SRT test within groups, the paired t-test was used. For between-group analysis, the independent t-test was applied. Results: The mean age of the subjects was 23.8±0.47 years. There were 10 males and five females in group A and eight males and seven females in group B. Significant differences were identified in the thickness of the hamstring muscles in both groups when analysed within groups (p-value=0.001). However, there was no significant difference in the between-group analysis (p>0.001). Conclusion: The study concluded that both Mulligan’s BLR and KCAT were equally effective and could be used as adjuncts in improving hamstring flexibility.